2021
DOI: 10.1177/13684302211038062
|View full text |Cite
|
Sign up to set email alerts
|

Following the best of us to help them: Group member prototypicality and collective action

Abstract: While considering the role of group-level factors as predictors of collective action, research has overlooked the role of group prototypes in determining willingness to engage in collective action. To begin to investigate this area, we conducted two correlational studies ( Ns = 141 and 98) in high schools examining the association between prototypical ingroup members’ desire to engage in collective action and participants’ collective action on behalf of a disadvantaged group (immigrants). Results showed a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The present results integrate and extend scarce research on collective action in young samples (e.g., Di Bernardo et al, 2021; McKeown & Taylor, 2022; Taylor & McKeown, 2021; Vezzali et al, 2021). Consistent with the developmental intergroup perspective, which places importance on group processes and adherence to group norms (Abrams & Rutland, 2008), we showed that a positive social identity is associated with moral considerations and indirectly to relevant social outcomes, such as helping disadvantaged people.…”
Section: Discussionsupporting
confidence: 88%
“…The present results integrate and extend scarce research on collective action in young samples (e.g., Di Bernardo et al, 2021; McKeown & Taylor, 2022; Taylor & McKeown, 2021; Vezzali et al, 2021). Consistent with the developmental intergroup perspective, which places importance on group processes and adherence to group norms (Abrams & Rutland, 2008), we showed that a positive social identity is associated with moral considerations and indirectly to relevant social outcomes, such as helping disadvantaged people.…”
Section: Discussionsupporting
confidence: 88%
“…Again, their effectiveness may be undermined by the fact that advantaged groups are usually motivated to maintain their privilege and the status quo and to resist attempts at social change (Osborne et al., 2019; Phillips & Lowery, 2018). This might lead to the perception that group members showing solidarity with disadvantaged groups and mobilizing for social change are not prototypical members of the group, thus limiting their influence (Di Bernardo et al., 2023; Knippenberg, 2019). Interestingly, research has found that advantaged group allies themselves show low levels of identification with their privileged ingroup (Lowery et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we did not assess the content of identity (such as its complexity or the values and moral traits characterizing it), which can instead be to understand how it relates to collective action (van Zomeren et al, 2018). For instance, a possible explanation for the key role played by common identification in the pursuit of social change can be found in the metacontrast principle (Turner et al, 1987), which can be used to calculate the degree of perceived prototypicality of the different subordinate identities (for an example of the use of the metacontrast principle applied to collective action, see Di Bernardo et al, 2023). It could be plausible that focusing on a broader social identity, individuals would be willing to engage in collective action only for highly prototypical subgroups.…”
Section: Discussionmentioning
confidence: 99%